2010
DOI: 10.3382/ps.2010-00628
|View full text |Cite
|
Sign up to set email alerts
|

Developmental phenotypic-genotypic associations of tyrosinase and melanocortin 1 receptor genes with changing profiles in chicken plumage pigmentation

Abstract: The tyrosinase (TYR) and melanocortin 1 receptor (MC1R) genes have been accepted as major genes involved in the plumage pigmentation of chickens. The co-segregation of plumage coloration and sequence polymorphism in TYR and MC1R genes were investigated using an intercross between black and white plumage color types of the Dongxiang blue-shelled chicken. Profiles of plumage color changing and genes expression levels of TYR and MC1R were observed from hatch to 112 d of age using quantitative real-time reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…One of the most significant markers (SNP AX-75379450) was located within the TYR gene, while a total of 10 significant SNPs were concentrated in a very small interval of 0.27 Mb within the GRM5 gene. TYR codes for a key enzyme in melanin biosynthesis and it has been accepted as a major gene involved in plumage color in chickens [22][23][24]. A previous study reported that TYR showed the greatest level of differential expression in the skin of black versus white chickens [24].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most significant markers (SNP AX-75379450) was located within the TYR gene, while a total of 10 significant SNPs were concentrated in a very small interval of 0.27 Mb within the GRM5 gene. TYR codes for a key enzyme in melanin biosynthesis and it has been accepted as a major gene involved in plumage color in chickens [22][23][24]. A previous study reported that TYR showed the greatest level of differential expression in the skin of black versus white chickens [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Liu et al (2010) studied Dongxiang black chicken from hatching to 112 days, and found that MC1R expression in skin peaked at 28 d and decreased thereafter. Dorshorst et al (2011) found that EDNRB2 expression was significantly different between adult black and non-black chicken, although the difference in EDNRB was non-significant.…”
Section: Discussionmentioning
confidence: 99%
“…After the report of (Oetting et al, 1985) that the C locus is the structural locus for tyrosinase in the fowl, the TYR gene was first cloned from chicken (Mochii et al, 1992). Previous studies have shown that mutations of the TYR gene are associated with albinism phenotype in many vertebrates, such as human (Fukai et al, 1995; Oetting, 2000), mouse (Yokoyama et al, 1990), rat (Blaszczyk et al, 2005), cat (Imes et al, 2006), rabbits (Aigner et al, 2000), cattle (Schmutz et al, 2004), chicken (Tobita-Teramoto et al, 2000; Sato et al, 2007; Liu et al, 2010). …”
Section: Introductionmentioning
confidence: 99%